2008
DOI: 10.4049/jimmunol.181.9.6664
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Aspartic Acid at Position 265 in the CH2 Domain for Murine IgG2a and IgG2b Fc-Associated Effector Functions

Abstract: Replacement of aspartic acid by alanine at position 265 (D265A) in mouse IgG1 results in a complete loss of interaction between this isotype and low-affinity IgG Fc receptors (FcγRIIB and FcγRIII). However, it has not yet been defined whether the D265A substitution could exhibit similar effects on the interaction with two other FcγR (FcγRI and FcγRIV) and on the activation of complement. To address this question, 34-3C anti-RBC IgG2a and IgG2b switch variants bearing the D265A mutation were generated, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 30 publications
2
88
0
Order By: Relevance
“…This unexpected observation shows that tumor targeting by the antibody variable region is dispensable for synergy with TA99. A single point mutation (D265A) in the antibody Fc region ablates interactions with FcγRs and complement, abolishing IgG effector functions (18). We introduced the D265A mutation to TA99-IL2 and sm3E-IL2 and found that the D265A immunocytokines did not perform significantly differently from their parent immunocytokines ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This unexpected observation shows that tumor targeting by the antibody variable region is dispensable for synergy with TA99. A single point mutation (D265A) in the antibody Fc region ablates interactions with FcγRs and complement, abolishing IgG effector functions (18). We introduced the D265A mutation to TA99-IL2 and sm3E-IL2 and found that the D265A immunocytokines did not perform significantly differently from their parent immunocytokines ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the 34-3C IgG2a F243A mutant, which contained ∼20% sialylated glycovariants, efficiently interacted with FcgRs and activated complement, and was as pathogenic as barely sialylated WT Ab (28). However, sialylated 6A6 IgG1 and IgG2b antiplatelet glycovariants enriched through SNA lectin affinity column chromatography were shown to be less pathogenic as compared with their poorly sialylated counterparts (25).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 34-3C IgG2a F243A displayed a markedly increased content of sialylated glycoforms, which accounted for ∼20% of total oligosaccharides, which contrasted with essentially absence of sialylated glycoforms (,1%) in WT 34-3C IgG2a mAb (28). Despite these remarkable differences in the content of sialylated glycoforms, the pathogenic activity of 34-3C IgG2a F243A mutant was comparable with that of WT 34-3C IgG2a.…”
Section: No Complement Activation By Agalactosylated 34-3c Igg1 Variantmentioning
confidence: 92%
See 1 more Smart Citation
“…The N297Q and the D265A mutations in the CH2 domain alter the oligosaccharide composition necessary for optimal recognition of IgG by human Fc gamma receptors, the former mutation by removing the site for N-linked carbohydrates 25 and the latter mutation by increasing galactosylation and sialylation. 26 In this respect, the L234A/L235A/K322A mutant is more similar to the G236R/L328R mutant, 21 in that they both target the key binding motif for C1q (K322A or L328R) as well as the motif involved in the high-affinity interaction with Fc gamma receptors, 27 likely without altering of the oligosaccharide composition.…”
Section: Discussionmentioning
confidence: 99%